Media preferences for public service assistance of selected residents of Bgy. East Timawa Molo, Iloilo City - Alimpuyo, Leonor Orchid; Estrada, Aidy.; Sepanton, Letecia; Tamayo, Lalaine Ian.; Tusi, Felicidad; Vocales, Lailanie (1998.)
Executive summary-This study "Media Preferences for Public Service Assistance of Selected Residents of Bgy. East Timawa, Molo, Iloilo City" in a descriptive research which aims to determine the media preferences for public service assistance of selected residents of Bgy. East Timawa, Molo, Iloilo City. The study likewise focuses on the level of media exposure and other factors which can affect their preferences. Measures rising from reasons and number of times for seeking asisstance was used. Mass media exposure was also measured in terms of the number of days per week and number of hours per day for listening, viewing or reading. Results show that respondents who are exposed to radio at an average of one to five hours a day, seven days a week prefer to seek assistance from radio stations. This references is made by women who are unemployed but finished or at least reached the college level. These respondents belong to 15-29 age group with no fixed income. The study also reveals that the sample owns and prefers radio to acquire information and for entertainment. Reasons of those who preferred the radio station are basically awareness of the assistance given to others as well as the assurance of immediate assistance, accessibility and convenience.
Research Paper (Mgt 200-Management Research) -- [Iloilo City] : University of the Philippines in the Visayas - College of Management, March 28, 1998.